Analisis Implementasi Kebijakan Bantuan Operasional Sekolah Tingkat Sekolah Dasar di Kabupaten Jember - Maharani, Ivana Septia; Kurniawan, Adi (Majalah Ilmiah DIAN ILMU, 2023)
The government program known as the School Operational Assistance Fund (BOS) was created by the redistribution of gasoline subsidy payments in the education sector. This program is to relieve students for children who actually can't afford them. The aim of this qualitative research, which uses a descriptive methodology, is to ascertain how the BOS policy is implemented at the elementary school level in Jember District. Utilization and distribution of BOS funds is where the problem lies. Efficiency and effectiveness of utilization is a problem because it hinders the ability of BOS funding to achieve its goals. Even when the BOS funds provided had been determined in terms of amounts and procedures, there were still delays in funding which caused schools to experience difficulties. Several schools asked parents for additional funds as a result of BOS not being sent. In order for the system or procedure for implementing BOS funds to function in accordance with what has been regulated and the objectives of implementing education can be achieved, it is necessary to increase the discipline of schools and BOS fund distributors.